Interstitial Lung Disease in Rheumatoid Arthritis in the Era of Biologics - A. Picchianti Diamanti; V. Germano; E. Bizzi; B. Laganà; A. Migliore (Pulmonary Medicine, 2011)
Interstitial lung disease (ILD) represents a severe manifestation in connective tissue diseases (CTD), with an overall incidence of 15%, and it is still a challenge for clinicians evaluation and management. ILD is the most common manifestation of lung involvement in Rheumatoid Arthritis (RA), observed in up to 80% of biopsies, 50% of chest Computed Tomography (CT) and only 5% of chest radiographs. Histopatological patterns of ILD in RA may present with different patterns, such as: usual interstitial pneumonia, non specific interstitial pneumonia, desquamative interstitial pneumonia, organizing pneumonia, and eosinophilic infiltration. The incidence of ILD in RA patients is not only related to the disease itself, many drugs may be in fact associated with the development of pulmonary damage. Some reports suggest a causative role for TNFα inhibitors in RA-ILD development/worsening, anyway, no definitive statement can be drawn thus data are incomplete and affected by several variables. A tight control (pulmonary function tests and/or HRCT) is mandatory in patients with preexisting ILD, but it should be also performed in those presenting risk factors for ILD and mild respiratory symptoms. Biologic therapy should be interrupted, and, after excluding triggering infections, corticosteroids should be administered.